The usage of different types of food outlets was not significantly associated with body mass index during the third COVID‐19 national lockdown in the United Kingdom - Ahmad Albalawi; Catherine Hambly; John R. Speakman (Wiley, 2022)
Abstract Background The United Kingdom (UK) implemented several national lockdowns during the coronavirus pandemic during which restaurants were closed and people were advised to stay at home if possible. These restrictions were eased and reapplied multiple times between March 2020 and May 2021. The change in restaurant access and prolonged restriction of activity may have an impact on body weight. Aim The aim of this study was to examine the impact of multiple lockdowns on body mass index (BMI) change from pre‐pandemic till during the third lockdown and on the use of different types of food outlets and their association with BMI change. Materials and Method Surveys of usage of different types of food outlets were distributed online before the lockdown between 06 January and 12 December 2019 and during the third national lockdown between 29 March and 25 April 2021. The food outlet usage surveys were filled out for seven consecutive days. Self‐reported BMI was reported before the pandemic and during the third phase of the lockdown. The total number of individuals who started the study before the pandemic was 681, and 60 participants completed the surveys during the third phase of lockdown. Results For the 60 participants in both surveys mean BMI was significantly higher during the third lockdown (28.6 ± 5.9 kg.m2) in comparison with the mean BMI before the pandemic 2019 (28.0 ± 5.5 kg.m2) (paired T = 3.09, p < 0.003). There was a significant positive association between BMI change, total number of days spent in lockdown (β = 0.05, p < 0.01, R2 = 9.99), and age (β = 0.06, p < 0.007, R2 = 11.8). There was no significant association between change in BMI and change in the frequency of using fast food restaurants (FFRs), full‐service restaurants (FSRs), and delivery and takeaways. Conclusion BMI was increased significantly during the lockdown in comparison with prior to the pandemic. Individuals gained more weight the longer they stayed at home during lockdowns, and physical activity was reduced to approximately half. However, the BMI change was not related to the change in use of different types of food outlets. This pattern does not support the widespread belief that visiting restaurants or using delivery and takeaway services has a significant impact on body weight.